FINTECH FOR SDGS: DRIVING ECONOMIC DEVELOPMENT THROUGH FINANCIAL INNOVATION - Wicaksana, Dwi Yoga; Dewi, Hapsari Shinta Citra Puspita; Erta, Erta (Universitas Negeri Surabaya, 2023)
This research delves into the pivotal role of Financial Technology (FinTech) in advancing the financial sector, sustainable development, and financial inclusion. Employing a descriptive-qualitative approach and the systematic literature review (SLR) method, the study investigates FinTech's interplay with Sustainable Development, Financial Inclusion, and Economic Development globally. A meticulous Scopus search utilizing keywords like